Development of a heterogeneous microwave network fade simulation tool applicable to networks that span Europe - Paulson, Kevin; Paulson, Kevin S.; Basarudin, Hafiz (RADIO SCIENCE, 2011)
Several research groups in Europe are developing joint channel simulators for arbitrarily complex networks of terrestrial and slant path, microwave telecommunications links. Currently, the Hull Rain Fade Network Simulator (HRFNS) developed at University of Hull can simulate rain fade on arbitrary terrestrial networks in the southern United Kingdom, producing joint rain fade time series with a 10 s integration time. This paper reports on work to broaden the function of the existing HRFNS to include slant paths such as Earth-space links and communications to high altitude platforms and unmanned airborne systems. The area of application of the new simulation tool is being extended to the whole of Europe, and other fade mechanisms are being included. Nimrod/OPERA has been chosen as the input meteorological data sets for the new system to simulate rain fade. Zero-degree isotherm heights taken from NCEP/NCAR Reanalysis Data are used in conjunction with the Eden-Bacon sleet (wet snow) model to introduce melting layer effects. Other fading mechanisms, including cloud fade, scintillation and absorption losses by atmospheric gasses, can be added to the simulator. The simulator is tested against ITU-R models for rain fade distribution experienced by terrestrial and Earth-space links in the southern United Kingdom. Statistics of fade dynamics, i.e., fade slope and fade duration, for a simulated Earth-space link are compared to International Telecommunication Union models.
Batch 005. Output ID 36430.
Keywords: Electrical and Electronic Engineering; General Earth and Planetary Sciences; Condensed Matter Physics